A Key Role for Prefrontocortical Small Conductance Calcium-Activated Potassium Channels in Stress Adaptation and Rapid Antidepressant Response. (3rd September 2019) - Bambico, Francis Rodriguez; Li, Zhuoliang; Creed, Meaghan; De Gregorio, Danilo; Diwan, Mustansir; Li, Jessica; McNeill, Sean; Gobbi, Gabriella; Raymond, Roger; Nobrega, José N
Abstract: The muscarinic acetylcholine receptor antagonist scopolamine elicits rapid antidepressant activity, but its underlying mechanism is not fully understood. In a chronic stress model, a single low-dose administration of scopolamine reversed depressive-like reactivity. This antidepressant-like effect was mediated via a muscarinic M1 receptor–SKC pathway because it was mimicked by intra-medial prefrontal cortex (intra-mPFC) infusions of scopolamine, of the M1 antagonist pirenzepine or of the SKC antagonist apamin, but not by the selective serotonin reuptake inhibitor (SSRI) antidepressant fluoxetine. Extracellular and whole-cell recordings revealed that scopolamine and ketamine attenuate the SKC-mediated action potential hyperpolarization current and rapidly enhance mPFC neuronal excitability within the therapeutically relevant time window. The SKC agonist 1-EBIO abrogated scopolamine-induced antidepressant activity at a dose that completely suppressed burst firing activity. Scopolamine also induced a slow-onset activation of raphe serotonergic neurons, which in turn was dependent on mPFC-induced neuroplasticity or excitatory input, since mPFC transection abolished this effect. These early behavioral and mPFC activational effects of scopolamine did not appear to depend on prefrontocortical brain-derived neurotrophic factor and serotonin-1A activity, classically linked to SSRIs, and suggest a novel mechanism associated with antidepressant response onset through SKC-mediated regulation of activity-dependent plasticity.